2010
DOI: 10.1258/acb.2009.009210
|View full text |Cite
|
Sign up to set email alerts
|

Application of five frozen human-pooled serum samples assigned by the International Federation of Clinical Chemistry and Laboratory Medicine reference procedure in a traceability investigation of γ-glutamyltransferase catalytic concentration measurements in China

Abstract: Background: The in vitro directive of the European Union requires traceability to the international recommended reference procedures. The application of the reference procedures is necessary in order to evaluate the accuracy of gglutamyltransferase (GGT) assays of routine measurement systems in China. Methods: Five frozen patient-pooled serum samples were assigned values by the International Federation of Clinical Chemistry and Laboratory Medicine (IFCC) reference procedure in order to evaluate the traceabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Several examples in literature show that the application of the metrological traceability approach works well in harmonizing enzyme results in clinical samples [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Several examples in literature show that the application of the metrological traceability approach works well in harmonizing enzyme results in clinical samples [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a proof-of-concept study should properly be performed to obtain convincing evidence that the standardization works by improving result comparability in clinical setting, in order to justify costs required to recalibrate assays due to manufacturing process changes, communications to regulatory agencies, etc. (49) .…”
Section: Role and Duties Of Diagnostic Manufacturersmentioning
confidence: 99%
“…Methods for detecting serum GGT include (a) a reference method recommended by the International Federation of Clinical Chemistry and Laboratory Medicine (IFCC) 7 which shows accurate measurement results, but the operation is tedious, time‐consuming, costly, and cannot be automated, making it unsuitable for routine detection of clinical patients samples, and (b) conventional measurement systems with simple operation, low‐cost, automation, and wide use. However, the results of conventional measurement systems are often inconsistent; Xia Cet al 8 showed deviation was as high as 14.2% compared to IFCC reference procedure and coefficients of variation between systems as high to 11.6%. Additionally, some systems are not consistent in the level of medical decision‐making 9 .…”
Section: Introductionmentioning
confidence: 99%